Agronomic traits of soybean cultivars released in different decades after grafting record‐yield cultivar as rootstock. (14th February 2017) - Li, Shengyou; Teng, Fei; Rao, Demin; Yao, Xingdong; Zhang, Huijun; Wang, Haiying; Song, Shuhong; St. Martin, Steven K.; Xie, Futi
Abstract: Breeders have seldom considered the selection for root traits during the genetic improvement in soybean. It is hypothesized that grain yield would be increased by the root function improvement, especially for the current cultivars. The objective of this grafting experiment was to determine the effect of record‐yield cultivars L14 or Z35 as rootstocks on agronomic traits of cultivars released in different decades. A total of 11 cultivars, released in different decades, were used to graft onto L14 or Z35 rootstocks. The agronomic traits were measured in the pot‐culture experiments. Grafting cultivars released in different decades onto L14 or Z35 rootstocks resulted in higher yield, 100‐seed mass and apparent harvest index as compared with those of non‐grafted or self‐grafted plants. Grain yield gain of cultivars grafted onto record‐yield cultivar rootstocks was 0.40 g/plant/year from 1966 to 2006, which was larger than that of non‐grafts and self‐grafts (0.27 g/plant/year). The yield of current cultivars should increase more if their root functions were improved.